Percaya Diri, Dukungan Sosial dan Kecemasan Siswa Menghadapi Seleksi Perguruan Tinggi - Djuwitawati, Sri; Djalali, M. As’ad (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
The goal of this research is to find the correlation between Self confidenceand social endorsement with students’ anxiety facing the University selectionprocess. 163 students of XI grade of SMA Negeri 6 Madiun become the subject,(consist of 68 boys and 95 girls). Researcher use three kinds of way in this researchthey are; students’anxiety facing the University selection process scale, selfconfidence scale and self endorsement scale. The research data analyzed withcorrelation analysis level Spearman’Rho. The research results are; 1) Selfconfidence with students’ anxiety facing University selection process is Rho 0,040and p = 0,610 (p < 0,05), it means there is no negative correlation with students’anxiety facing the University selection process. 2) social endorsement withstudents’anxiety facing the University selection process resulted Rho 0,444 and p =0,000 (p < 0,05), it means social endorsement has positive correlation betweenstudents’ anxiety facing the University selection process.Keywords : self confidence, social endorsement, and students’anxiety in facing theUniversity selection process.